Microjaponin, A New Dihydroagarofuranoid Sesquiterpene from the Stem of Microtropis japonica with Antituberculosis Activity. Issue 8 (August 2014) - Chen, Jih‐Jung; Kuo, Wen‐Lung; Chen, Ih‐Sheng; Peng, Chien‐Fang; Sung, Ping‐Jyun; Cheng, Ming‐Jen; Lim, Yun‐Ping
Abstract A new dihydroagarofuran‐based sesquiterpene, microjaponin (1), was isolated from the stem of Microtropis japonica. Its structure was determined by in‐depth spectroscopic and mass‐spectrometric analyses. Microjaponin (1) exhibited potent in vitro antituberculosis activity, with an MIC value of 12.5 μg/ml against Mycobacterium tuberculosis H37Rv.